The crystal structure of ethyl (Z)-2-(ethoxymethylene)-3-oxobutanoate, C9H14O4 - Hentsch Andreas; Merzweiler Kurt (Zeitschrift für Kristallographie - New Crystal Structures, 2024)
C9H14O4, monoclinic, P21/n (no. 14), a = 8.9332(5) Å, b = 6.8170(2) Å, c = 17.0530(9) Å, β = 102.816(4)°, V = 1,012.62(8) Å3, Z = 4, R[F 2 > 2σ(F 2)] = 0.0363, wR(F 2) = 0.1046, T = 170 K.